2021
DOI: 10.4266/acc.2021.00605
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D deficiency with COVID-19 severity and mortality in Iranian people: a prospective observational study

Abstract: Background: As the coronavirus disease 2019 (COVID-19) pandemic continues to escalate, it is important to identify the prognostic factors related to increased mortality and disease severity. To assess the possible associations of vitamin D level with disease severity and survival, we studied 248 hospitalized COVID-19 patients in a single center in a prospective observational study from October 2020 to May 2021 in Tehran, Iran. Methods: Patients who had a record of their 25-hydroxyvitamin D level measured in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…After deleting duplicates, we identified 2463 studies from four databases and then screened articles by title and full text according to the study's objectives. Finally, 69 studies were included in the meta-analysis (Figure 1), of which 62 studies had assessed risk factors for death from COVID 2889 ); 13 studies determined risk factors for severity (( 41,50,5355,65,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After deleting duplicates, we identified 2463 studies from four databases and then screened articles by title and full text according to the study's objectives. Finally, 69 studies were included in the meta-analysis (Figure 1), of which 62 studies had assessed risk factors for death from COVID 2889 ); 13 studies determined risk factors for severity (( 41,50,5355,65,…”
Section: Resultsmentioning
confidence: 99%
“…After deleting duplicates, we identified 2463 studies from four databases and then screened articles by title and full text according to the study's objectives. Finally, 69 studies were included in the meta-analysis (Figure 1), of which 62 studies had assessed risk factors for death from COVID ); 13 studies determined risk factors for severity (( 41,50,[53][54][55]65,[90][91][92][93][94][95][96] ), out of which six studies reported both outcomes ( (35,44,(47)(48)(49)59)). Out of 69 studies, 33 were cohort studies, eight were case-control studies, and 28 were cross-sectional studies.…”
Section: Search Results and Quality Assessmentmentioning
confidence: 99%
“…8 According to some studies, serum concentrations of 25(OH)D were inversely associated with pro-inflammatory cytokines, IL-6, CRP and the risk of pneumonia, acute respiratory distress syndrome (ARDS), diabetes and heart failure. 18,19 Biomarkers have been used for confirming and classifying disease severity in COVID-19 and according to some investigators, CRP was elevated in 60.7% of patients, PCT in 5.5%, and LDH in 41% of patients. 19 Patients with severe COVID-19 have a higher incidence of elevated CRP than those with a mild form of disease.…”
Section: Sample Sizementioning
confidence: 99%
“…19 Another study showed findings to the contrary, that ferritin levels could predict severe disease and mortality. 18 A small retrospective study revealed that ferritin was the last parameter to return to normal making it a marker of severity and less useful for monitoring the course of disease. 24 In our investigation, the insignificant baseline levels of ferritin, LDH and procalcitonin may reflect an earlier course of their disease, while the insignificant decrease in markers from the initial results could be due to coexisting infections or comorbidities and that other repeated levels of inflammatory parameters (between baseline and final values) were not taken into account during the course of their hospitalization.…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…This may be because micronutrients can participate in regulating the immune response in the body, and their deficiency will cause immune imbalance in the body, and then induce various diseases [ 9 , 10 ]. It has been reported that vitamin D insufficiency was closely related to the risk and severity of COVID-19 infection [ [11] , [12] , [13] , [14] , [15] , [16] ]. However, whether other micronutrients have an impact on COVID-19 infection is largely unknown.…”
Section: Introductionmentioning
confidence: 99%